Indonesian EFL Students’ Perceptions on Learning Autonomy in Online Learning Delivery Mode - Dalilan Dalilan (Institut Agama Islam Negeri Madura, 2021)
The online learning delivery method is increasingly used in the teaching and learning process at universities. This type of learning is relatively new to students, in particular to Indonesian EFL students. Students' learning autonomy in an online learning system is inevitably required. Autonomy in online learning and in offline learning can be differently perceived by the students. This study aimed at revealing EFL students' perception on learning autonomy in an online learning method. A questionnaire was used as the single instrument to obtain data from 35 students of the English Education Study Program of Tarbiyah and Teacher Education Faculty, State Islamic University Raden Fatah Palembang. The study sample was selected using opportunity sampling, and data were analyzed using a simple percentage statistic formula. The study results indicated that the majority of the students perceive online learning as independent learning in which they must have self-learning awareness and motivation, self-learning responsibility, and self-directed and governed learning. They also perceived that they could develop the problem-solving ability, critical thinking, and learning initiative in autonomous online learning. In the context of learning independently in an online learning system, self-time management is also essential to support their learning optimally.